Comparison of the prevalence of disabilities based on self-reports among Latin American countries - Monteverde-Verdenelli, Malena (2014)
In general, the measurement of the prevalence of disability at population level or large samples is based on self-reports. It is of interest to assess the extent to which self-reports allow comparisons between population groups. The aim of this study is to measure, compare and analyze the consistency of the comparisons of the prevalence of disability in activities of daily living (ADL) among populations in Latin America. The analysis includes the cities of Buenos Aires, Santiago de Chile, Sao Paulo, Mexico City, Montevideo and Havana. In order to evaluate the consistency of comparisons based on self-reports, we estimate prevalence of disability in ADLs and prevalence of disability-related chronic diseases and we compare patrons among country with both conditions. Populations aged 60 and over in Buenos Aires and Montevideo report lower prevalence of disabilities in ADLs and lower prevalence of chronic disabling conditions such as diabetes, lung disease, stroke and cognitive problems. This suggests that at least part of the differences in self-reported disabilities may be due to differences in morbidity. However, it does not rule out the existence of other effects such as those due to differences in contextual factors or in the propensity to report disabilities. In this sense, it would be useful to conduct ad-hoc studies to measure simultaneously self-reported and diagnoses conditions, the use of instruments such as vignettes and the introduction of questions about contextual factors (at least for sub-samples), in order to assess the existence of bias and the importance of contextual factors in self-reports of disabilities.